2006
DOI: 10.1128/aem.72.3.2155-2162.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Distinct l -Methionine Catabolic Pathways in the Yeast Geotrichum candidum and the Bacterium Brevibacterium linens

Abstract: Tracing experiments were carried out to identify volatile and nonvolatile L-methionine degradation intermediates and end products in the yeast Geotrichum candidum and in the bacterium Brevibacterium linens, both of which are present in the surface flora of certain soft cheeses and contribute to the ripening reactions. Since the acid-sensitive bacterium B. linens is known to produce larger amounts and a greater variety of volatile sulfur compounds (VSCs) than the yeast G. candidum produces, we examined whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…4-methylthio-2-oxobutyric acid (KMBA). It has been characterized in a variety of animals (22), in yeasts (23,24), and in Lactococcus lactis (25). [ 13 C]-NMR studies performed in yeast cells indicated that KMBA was mainly decarboxylated then reduced to produce methionol or, in a lower extent, cleaved by a demethiolase activity to produce CH 3 SH and ␣KB.…”
Section: Discussionmentioning
confidence: 99%
“…4-methylthio-2-oxobutyric acid (KMBA). It has been characterized in a variety of animals (22), in yeasts (23,24), and in Lactococcus lactis (25). [ 13 C]-NMR studies performed in yeast cells indicated that KMBA was mainly decarboxylated then reduced to produce methionol or, in a lower extent, cleaved by a demethiolase activity to produce CH 3 SH and ␣KB.…”
Section: Discussionmentioning
confidence: 99%
“…To compensate the secondary loss of MGL, these bacteria might utilize an alternative pathway, as shown in yeast G. candidum. In this pathway, methionine degradation is initiated by transamidation, which forms 4-methylthio-2-oxobutyrate, followed by a cleavage to yield 2-oxobutyrate and methanethiol by chemical process (44). The comparative metabolomics and fluxomics between the bacteria possessing or lacking MGL should help our understanding its biological importance of MGLs.…”
Section: Perspectivesmentioning
confidence: 99%
“…Methanethiol is converted to dimethyl disulfide, dimethyl trisulfide, and thioesters, and 2-oxobutyrate is condensed with active acetaldehyde derived from pyruvate, and metabolized to 2,3-pentanedione (acetyl propionyl) (44). This condensation reaction is catalyzed by acetolactate synthase (44,45).…”
Section: The Other Roles Of Mgl In Bacteriamentioning
confidence: 99%
See 2 more Smart Citations